Factors predicting smoking cessation among higher education students at Tha Sala District in Nakhon Si Thammarat Province - Luksanavimon, Luksamon; Petsirasan, Rewwadee (Thai Journal of Nursing, 2022)
This cross- sectional design aimed to examine the predicting factors of smoking cessation of higher education students at Tha Sala District in Nakhon Si Thammarat Province. A sample of 198 first-year male students, was purposively selected. Data collected during September to November 2563 BE by using self-administered questionnaire including general information, perception on quitting smoking, opinion toward the policy on smoking cessation in higher education institutions, and perception on the Tobacco Products Control Act, B.E. 2560. Descriptive statistics and Binary logistic regression analysis were employed for data analysis. The results indicated that students’ smoking behaviors were ever smoking (57.56%), currently quit smoking (44.95%), quit smoking more than six months (18.69%). The information smoking cessation from public health personnel was obtained 45.61%, and from university campaign 14.00%. Quit smoking immediately 64.04% were used. The predicting factors of smoking cessation were sufficient income, quit smoking decision, and smoking replacement at p < .05.